Comparison of the Neer classification to the 2018 update of the Orthopedic Trauma Association/AO fracture classification for classifying proximal humerus fractures. Issue 3 (18th September 2022) - Marmor, Meir T.; Agel, Julie; Dumpe, Jarrod; Kellam, James F.; Marecek, Geoffrey S.; Meinberg, Eric; Nguyen, Mai P.; Sims, Stephen; Soles, Gillian L.; Karam, Matthew D.
Abstract: Background: The classification of fractures is necessary to ensure a reliable means of communication for clinical interaction, education and research. The Neer classification is the most commonly used classification for proximal humerus fractures. In 2018 the Orthopedic Trauma Association (OTA) and the AO Foundation provided an update to the OTA/AO Fracture Classification Scheme addressing many of the concerns about the previous versions of the classification. The objective of the present study was to evaluate the rater reliability of the 2 classifications and if the classifications subjectively better characterized the fracture patterns. Methods: X-rays and CT scans of 24 proximal humerus fractures were given to 7 independent raters for classification according to the Neer and 2018 OTA/AO classification. Both full-forms and short-forms of the classifications were tested. The Fleiss Kappa statistic was used to assess inter-rater agreement and intra-rater consistency for the 2 classifications. For each case the raters subjectively commented on how well each classification was able to characterize the fracture pattern. Results: All raters graded the 2018 OTA/AO classification as good as or better than the Neer classification for an adequate description of the fracture patterns. The short-form 2018 OTA/AO classification had the most 4 rater and 5 rater agreement cases and the second most 6 rater agreement cases. The short-form Neer classification had the second most 4 rater and 5 rater agreement cases and the most 6 rater agreement cases. The full 2018 OTA/AO had the least 4, 5, or 6 rater agreement cases of all the classification systems. Inter-rater agreement was fair for the full and short form of both the Neer and 2018 OTA/AO classification. The full and short Neer classifications together with the short 2018 OTA/AO classification had moderate intra-rater consistency, while the full 2018 OTA/AO classification only had slight intra-rater consistency. Conclusions: The 2018 OTA/AO classification is equivalent in its short-form to the Neer classification in inter-rater reliability and intra-rater consistency; and is superior in its full form for characterizing specific fracture types. The low inter-rater reliability of the full 2018 OTA/AO classification is a concern that may need to be addressed in the future.